1998
DOI: 10.1111/j.1740-8261.1998.tb01616.x
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Ultrasound of the Prostate in Normal Dogs and in Dogs With Chronic Lymphocytic‐lymphoplasmocytic Prostatitis

Abstract: The prostate gland of 11 normal dogs and five dogs with histologically confirmed chronic lymphocytic or lymphoplasmocytic prostatitis were imaged with grey-scale and Doppler ultrasound. Three vessel types (prostatic artery, capsular artery and parenchymal artery) were identified with color Doppler and the resistive index and maximum and minimum velocities were measured with pulsed wave Doppler. No differences between normal dogs and dogs with prostatitis was identified in either grey-scale ultrasound or in any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 15 publications
2
27
0
2
Order By: Relevance
“…The prostatic artery is a small-diameter vessel that provides blood supply for each lobe of the canine prostate independently. The artery either enters the capsule on the dorsolateral surface, forming a branched parenchymal vascular net, or moves laterally to the gland and is derived from the urethral branch [7,24]. Even without global standardization of the terms used for the prostatic artery, this study used the anatomic vascular description to systematically name the locations studied.…”
Section: Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…The prostatic artery is a small-diameter vessel that provides blood supply for each lobe of the canine prostate independently. The artery either enters the capsule on the dorsolateral surface, forming a branched parenchymal vascular net, or moves laterally to the gland and is derived from the urethral branch [7,24]. Even without global standardization of the terms used for the prostatic artery, this study used the anatomic vascular description to systematically name the locations studied.…”
Section: Groupmentioning
confidence: 99%
“…Studies based on small or nonhomogeneous groups of dogs of different breeds and sizes have been conducted to identify the location of the canine prostatic artery and characterize the Doppler pattern in different locations [7][8][9][10][11]. One of these studies reported that there are differences between prostatic artery Doppler characteristics according to location, but no relationship was found between these characteristics and the age of the animal [8].…”
Section: Introductionmentioning
confidence: 96%
“…3-D visualization of the prostate, including volume-and surface-rendered data, are used and accepted by clinicians (Holmes and Robb, 2000). Three arterial types (prostate, capsular, and parenchymal) have been identified with color-Doppler US (Newell et al, 1998). Cranial (a. ductus deferentis), lateral (a. prostatica), and subcapsular arteries have been found with color-coded and pulsed Doppler sonography (Gü nsel- Apel et al, 2001).…”
Section: Clinical Significance Of Prostate Morphology Imaging Morphologymentioning
confidence: 99%
“…Subsequently, the dog species has been shown to be susceptible to prostate disease, and it is appearing with increasing frequency (Kraewiec and Helfin, 1992). Diagnostic testing currently consists of non-invasive methods for examining prostate vessels (Gü nzel-Apel et al, 2001;Hagen et al, 2001;Newell et al, 1998). New imaging techniques reveal the full complement of prostatic vessels, necessitating a more complete and consistent anatomical description and terminology for the extraglandular vascularization of the prostate and adjacent tissues and organs.…”
Section: Introductionmentioning
confidence: 98%
“…Da artéria urogenital originam-se diversos ramos prostáticos que entram na glândula prostática em sua superfície dorsolateral (NEWELL et al, 1998). Ramos das artérias prostáticas penetram na cápsula, tornando-se subcapsulares e caminham ao longo do septo, profundamente na glândula.…”
Section: Revisão De Literaturaunclassified